PENGEMBANGAN LKPD BERBASIS WORDWALL MENGGUNAKAN METODE TEAMS GAMES TOURNAMENT (TGT) SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 104607 SEI ROTAN - Feggy Putri Anggraini; Safrida Napitupulu (STKIP Subang, 2024)
The aim of this research is to produce, analyze the validity and practicality of Wordwall-based LKPD for the Teams Games Tournament (TGT) method in science and science learning. Material on the influence of force on objects for class IV SD Negeri 104607 Sei Rotan. This research uses the ADDIE development model. The subjects in this research were fourth grade students at SD Negeri 104607 Sei Rotan. The object of this research is the learning tools developed. Based on the results of research in the development of Wordwall-Based LKPD Using the Teams Games Tournament (TGT) Method in Science Learning Material on the Influence of Forces on Objects for Class IV SD Negeri 104607 Sei Rattan carried out by researchers, it can be concluded that the Wordwall-Based LKPD Uses the Teams Games Tournament (TGT) Method in Science and Science Learning Material: The Influence of Forces on Objects for Class IV SD Negeri 104607 Sei Rattan is suitable and valid for use.